Ethical and legal aspects of doctors’ activities on social media: A literature review - I Wayan Tunjung; I Made Putra Biantara (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Social media has become an essential communication platform influencing medical professionalism. For doctors, it serves as a tool for education, health promotion, and professional networking. However, unregulated use poses legal and ethical challenges, particularly concerning confidentiality and professionalism. This study explores the legal and ethical implications of doctors’ activities on social media in Indonesia. Methods: This research employs a normative legal and literature review approach. Sources were obtained from Google Scholar, PubMed, ScienceDirect, Garuda, and Sinta, using keywords such as doctor, social media, ethics, and health law. Articles published between 2020 and 2025 were selected based on relevance to legal and ethical aspects of medical social media use. Results: Findings indicate that while social media enhances accessibility to health information, education, and patient engagement, it also introduces risks of privacy breaches, misinformation, and blurred doctor–patient boundaries. Indonesian regulations, such as Law No. 11/2008 (ITE Law) and Law No. 17/2023 (Health Law), partially address these issues, but no specific regulation governs doctors’ digital conduct. A comparative analysis with international guidelines, such as those of the General Medical Council (UK), underscores the need for clearer national standards. Ethical principles in the Indonesian Medical Code of Ethics (KODEKI) must guide doctors’ online presence. Strengthened digital professionalism, legal clarity, and continuous education are crucial. Conclusion: Doctors’ responsible use of social media can enhance public health communication. However, comprehensive legal frameworks and ethical awareness are vital to safeguard patient rights and uphold medical professionalism in the digital era.